Impact of Usher syndrome on athletic performance - navigating silence and darkness - Rosiński, Mateusz; Rosińska, Kamila; Łojewska, Julia Natalia; Janicka, Ewelina Justyna; Perko, Agnieszka; Niedźwiedzka, Monika; Bochenek, Oliwia; Andrzejczyk, Agata (Quality in Sport, 2024)
Usher syndrome (USH) is an autosomal recessive genetic disorder and a leading cause of simultaneous hearing and vision loss. The aim of this paper is to provide a detailed review of Usher syndrome, including its pathogenesis, clinical symptoms, diagnostic methods, the role of sport in the lives of athletes and sportspeople with Usher syndrome and available therapeutic options. Understanding this disease is crucial for early detection and the implementation of appropriate therapeutic interventions. Currently, Usher syndrome is classified into three main types (I, II, and III), differentiated by the degree and progression of hearing and vision loss. Type I is characterized by profound congenital deafness and early-onset retinitis pigmentosa. Type II presents with moderate to severe hearing loss and later onset of visual problems. Type III is the rarest, with progressive hearing and vision loss that occurs later in life. The genetic basis of Usher syndrome is linked to mutations in various genes that affect proteins essential for the proper functioning of the inner ear and retina. Early diagnosis and an interdisciplinary approach to treatment are key to improving the quality of life for those affected by this disease. Ongoing research into the genetic mechanisms and potential therapies offers hope for future successful treatments.